Customer experience audit of retail chains in the Czech Republic - Zvoníček, Jan (2024)
This master's thesis focuses on mapping and comparing customer experience in brick-and-mortar stores between the companies Albert Česká republika, s.r.o. and Tesco Stores ČR a.s. The thesis is divided into theoretical and practical parts. The theoretical part deals with service marketing, defining customer experience, servicescape, and the measurement of customer experience. In the practical part, the companies Albert and Tesco are introduced, and the level and quality of customer experience between them are compared. The main contribution of the thesis consists of recommendations and proposals for improving customer experience for the given chains. These recommendations arise from the results of the CX audit conducted using mystery shopping and from the results of expert interviews conducted with representatives of the respective chains.